Radiation characteristics of one-dimensional periodic leaky-wave antennas - Majumder, S.; Jackson, D.R. (1997 IEEE Antennas and Propagation Society Meeting, 1997)
The subject of this paper is the study of the radiation properties of a one-dimensional periodic strip grating leaky-wave antenna when excited by a practical feed. The antenna structure, known as the dielectric-inset waveguide leaky-wave antenna has been proposed because of its mechanical simplicity, low loss and flexible radiation characteristics. A rigorous analysis of the antenna structure is introduced, which accounts for the feed excitation, the finite baffle length, and the finite length of the radiating aperture. The effects of the finite baffle height and aperture length are studied, and patterns are compared with those predicted from a simpler analysis based solely on the dominant leaky-wave, which neglects the effects of the feed radiation. Calculated radiation patterns are also compared with measured ones.